Overcoming Implementation Challenges: A Comprehensive Review of ASEAN Medical Device Directive (AMDD) Regulatory Harmonization - Vetrivel, Karthikeyan; Mahalingam, Murugappan; Elango, Vivekanandan; Mansor, Yusuf; Nikam, Kshitija Dilip (Indian Journal of Pharmaceutical Education and Research)
The challenges of AMDD implantation across Southeast Asia are uniformly bringing medical device regulations better in line to improve the safety of patients while reducing regulatory hurdles and boosting regional trade. By using a mixed-methods approach-literature review, stakeholder interviews and the study reveals important barriers: inconsistencies in regulations, technical challenges, resource limitations, economic effects, post-market surveillance issues and language differences. The paper discusses the distinctive regional factors in ASEAN by comparing the implementation of AMDD and sharing some experiences from the FDA and European Union Medical Device Regulation. It calls for addressing the challenges through collaboration, capacity building, phase-in implementation and technology solutions. The expected timeline for the full implementation of AMDD has also been considered in this paper to discuss subsequent consequences for the ASEAN medical device market and the overall healthcare systems. These recommendations now form the salient inputs for the policymakers, regulators and industry participants on how committed engagement and flexible strategies will be required to fulfill the broader objectives of the AMDD in terms of better health outcomes and economic development for the region.
Keywords: ASEAN Medical Device Directive (AMDD); Implementation challenges; Patient Safety; Regulatory harmonization; Southeast Asia.